Identification and characterization of yeasts isolated from oleic ecosystems - Romo-Sanchez, Sheila; Alves-Baffi, Milla [UNESP]; Arevalo-Villena, Maria; Ubeda-Iranzo, Juan; Briones-Perez, Ana; MendezVilas, A. (World Scientific Publ Co Pte Ltd, 2011)
The population dynamics of yeasts in oleic ecosystems in the Castilla la Mancha region (Spain) was analysed for two consecutive years (2007 to 2008) in two different varieties (Cornicabra and Arbequina respectively). Yeasts were isolated from of fresh olives (Olea europaea L.) fruits, olive pomace (solid waste) and olive paste (crush olives). All yeast species were identified by RFLPs of their rDNA but in some species sequence analysis of the 5.8S rDNA gene was necessary. This study allowed to identify 108 yeast isolated which belonging to seven different genera (Zygosaccharomyces, Pichia, Lachancea, Kluyveromyces, Saccharomyces, Candida, Torulaspora) and fourteen species. The most representative species were Pichia caribbica, Zygosaccharomyces fermentati and Pichia holstii. The yeast characterization was studied by means of several enzymes how beta-glucosidase, beta-glucanase, carbokymethylcellulase, polygalacturonase, peroxydase and lipase and was observed that the mayority of them presented beta-glucanase, beta-glucosidase and peroxidase activities, a few had cellulase and polygalacturonase activities and none of species showed lipase activity.
Keywords: yeast; enzymes; oleic ecosystems; olive paste; olive pomace; fresh olives